A randomised double-blind clinical trial of acyclovir (Zovirax) and adenine arabinoside in herpes simplex corneal ulceration. Issue 6 (June 1982) - Young, B J; Patterson, A; Ravenscroft, T
Abstract : A double-blind clinical trial of 3% acyclovir (Zovirax) and 3% adenosine arabinoside (ara-A, Vidarabine) in 93 patients with herpetic corneal ulceration is presented. Ulcers in 45 (94%) of acyclovir-treated patients and 37 (82%) ara-A-treated patients healed within 14 days. Patients treated with acyclovir healed more rapidly than those treated with ara-A (p less than 0.01). No serious adverse effects were observed.